Macromolecules containing metal and metal-like elements (John Wiley & Sons, 2003)
This book provides useful descriptions of applications for the reader to apply in his/her research into materials, polymers, and medicine/drug development. It covers non-linear optical materials, speciality magnetic materials, liquid crystals, anticancer and antiviral drugs, treatment of arthritis, antibacterial drugs, antifouling materials, treatment of certain vitamin deficiencies, electrical conductors and semiconductors, piezoelectronic materials, electrodes, UV absorption applications, super-strength materials, special lubricants and gaskets, selective catalytic and multisite catalytic agents